Geležinkelio ruožo Vilnius–Turmantas senųjų pastatų architektūra: tarp išnykimo ir išlikimo - Vrubliauskas, Dalius (Journal of Architecture and Urbanism, 2010)
The architecture of ancient buildings at the railroad section Vilnius–Turmantas: between extinction and SurvivaThe paper is aiming at attracting attention to the rapidly disappearing segment of cultural heritage – part of technical heritage – the buildings of the railroad infrastructure and their culturalhistoric, architectural values. Also, an attempt has been made to study the condition of these buildings at present and foresee their development prospects. The oldest railroad section in the territory of Lithuania, at present named as Vilnius–Turmantas (a part of the former railroad St. Petersburg–Warsaw) soon is going to celebrate its 150th anniversary. That is one of the largest construction projects of the middle of the 19th century, executed in the territory of Lithuania, which deserves to be regarded as a unique one because of its outstanding engineering and architectural idea, its scale and effects on economic and social development of the enclosed area and history of the whole region. However, the present condition of the most sensitive elements of the section’s content – its buildings – can be evaluated as lamentable, and most of them, as objects of a large complex of architectural and technical heritage, need urgent and specialized measures in order to be protected from being lost irreversibly.Article in Lithuanian.Santrauka. Straipsniu atkreipiamas dėmesys į sparčiai nykstančio kultūros paveldo segmento –  technikos paveldo dalies – geležinkelio infrastruktūros pastatų kultūrinę, istorinę, architektūrinę vertes, taip pat nagrinėjama šių pastatų esamos padėties būklė bei galimos raidos perspektyvos. Seniausio plačiojo geležinkelio ruožo Lietuvos teritorijoje atšaka, dabartiniu metu vadinama Vilnius–Turmantas (buv. Sankt Peterburgas–Varšuva), greitai minės garbų 150ies metų jubiliejų. Tai vienas stambiausių XIX a. vidurio statybos projektų Lietuvos teritorijoje, savo inžinierinės minties ir architektūros mastu bei ekonomikos ir socialinės srities raidos efektu nusipelno būti vadinamas unikaliu savo įtaka regiono istorijai. Tačiau dabartinė šio ruožo pastatų būklė išties yra apverktina. Daugeliui iš jų kaip architektūros ir techninio paveldo komplekso objektams reikalinga skubi, specializuota pagalba, kad šie objektai nebūtų prarasti negrįžtamai.Reikšminiai žodžiai: architektūros ir technikos paveldas, vietovės savitumo ženklai, kraštovaizdžio kaita, LR NKVAĮ, restauravimas, autentiškumas, įvaizdis, kultūrinis turizmas, mokymas (edukacija).